Local Stress Evaluation During Deformation in SUS304 Austenitic Stainless Steel. (2015) - Chen, M.; Matsumoto, A.; Shibata, A.; Terada, D.; Miyazawa, T.; Sato, M.; Adachi, H.; Tsuji, N.
Abstract: In this study, the local stress in an SUS304 austenitic stainless steel was measured during tensile deformation by a technique called energy dispersive X-ray diffraction microscopy using synchrotron radiation X-ray diffraction in SPring-8. The local stress evolution of two positions in different grains, respectively, were shown in this paper. At one position, the tensile component of principal stress increased with increasing the tensile strain, but slightly deviated from the macroscopic tensile direction. On the other hand, at another position, the tensile component of principal stress was substantially different from the macroscopic tensile direction, and the drastic change in direction of local stress were observed due to martensitic transformation.